ANALISIS HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN CAPAIAN BELAJAR SISWA SD DI MASA COVID-19 - Yudhi Pratama; Sukisno Sukisno (TSURAYYA: Journal Education, Economy and Religia, 2026)
This study examines the relationship between mothers’ educational level and the academic achievement of fourth-grade students at SDN 4 Karangjati, Blora, during the pandemic period. The background of the research emphasizes the role of parents, especially mothers, in children’s education, as mothers tend to interact more frequently with their children and manage household activities. The method used is quantitative, employing descriptive analysis and the Product Moment correlation technique with SPSS 15. The research population consists of all fourth-grade students in the first semester of the 2020/2021 academic year. Data were collected through questionnaires (to measure mothers’ education level) and documentation (student report card scores to measure academic achievement). The results of the study indicate that the average academic achievement score of Class VA students (77.15) falls within the medium qualification. Most of the students’ mothers (53.84%) have a high school or equivalent level of education. The Product Moment correlation result is 0.395 or 39.5%, with a significance level lower than 0.05, indicating a positive relationship between mothers’ educational level and students’ academic achievement.